2023
DOI: 10.1039/d2cp05357h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of fullerene-supported La2O3–C60 nanocomposites: dual-functional materials for photocatalysis and supercapacitor electrodes

Abstract: Nowadays, water pollution and energy crises worldwide force researchers to develop multi-functional and highly efficient nanomaterials. In this scenario, the present work reports dual-functional core-shell La2O3@C60 nanocomposite synthesized via the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Specific capacitance was calculated from the discharge components of GCD curves and calculated capacitances at different current densities is shown in Fig. 7 c. It was observed that similar to Co and Ni samples, drop in capacitance was observed for CoNi when current density was increased this can be due to the diffusion and penetration of electrolyte solution’s ions at much higher current densities 40 42 . However, it can be witnessed that CoNi based active material displayed excellent capacity retention at higher current densities where specific capacitance value dropped moderately from around 176 F/g at current density of 1 A/g to around 122 F/g when current density was increased by around ten times to 10 A/g.…”
Section: Resultsmentioning
confidence: 92%
“…Specific capacitance was calculated from the discharge components of GCD curves and calculated capacitances at different current densities is shown in Fig. 7 c. It was observed that similar to Co and Ni samples, drop in capacitance was observed for CoNi when current density was increased this can be due to the diffusion and penetration of electrolyte solution’s ions at much higher current densities 40 42 . However, it can be witnessed that CoNi based active material displayed excellent capacity retention at higher current densities where specific capacitance value dropped moderately from around 176 F/g at current density of 1 A/g to around 122 F/g when current density was increased by around ten times to 10 A/g.…”
Section: Resultsmentioning
confidence: 92%
“…7 (c). It was observed that similar to Co and Ni samples, drop in capacitance was observed for CoNi when current density was increased this can be due to the diffusion and penetration of electrolyte solution's ions at much higher current densities [33][34][35] . However, it can be witnessed that CoNi based active material displayed excellent capacity retention at higher current densities where speci c capacity value dropped moderately from around 176F/g at current density of 1A/g to around 122F/g when current density was increased by around ten times to 10 A/g.…”
mentioning
confidence: 83%
“…In 2023, Iqbal and co‐workers fabricated dual‐functional La 2 O 3 –C 60 nanocomposites for photocatalysts and electrode material for supercapacitors. [ 254 ] Thanks to the lower energy band gap, presence of deep‐level emissions, and lower recombination rate of photogenerated charge carriers compared to bare La 2 O 3 , the composites exhibited enhanced photocatalytic activity, as well as improved specific capacitance, outstanding energy density, and excellent stability for up to 5000 cycles in a 1 m KOH electrolyte.…”
Section: Carbon‐based Electrodes For Supercapacitorsmentioning
confidence: 99%